(untitled) (Balthazar, 2022)
This paper examines the relationship of the italian activist Mario Mieli with psychoanalysis, in order to define him as a "queer-Freudian philosopher", as well as a refined and innovative interpreter of Freud’s work: for this purpose, I first clarify the queerness elements contained in the Three Essays on Sexual Theory, brilliantly reinterpreted in Mieli’s Towards A Gay Communism: Elements of a Homosexual Critique. The theory of psychic hermaphroditism and constitutional bisexuality is articulated with the “educastrated” homoeroticism, filtered through the Marcusian lens of Freudo-Marxism that mediates Mieli’s reception of Freud. The second path I pursue concerns the de-pathologisation of schizophrenia and the investigation of the homosexuality-suicide nexus through the three "clinical cases" of Mario Mieli, the Freudian homosexual Dora, and the Foucauldian Herculine.